2009
DOI: 10.1021/nn900984w
|View full text |Cite
|
Sign up to set email alerts
|

Dip-Pen Nanolithography of Electrical Contacts to Single-Walled Carbon Nanotubes

Abstract: This paper discusses a method for the direct patterning of Au electrodes at nanoscale resolution using dip-pen nanolithography, with proof-of-concept demonstrated by creating single-walled carbon nanotube devices. This technique enables insight into three key concepts at the nanoscale: using dip-pen nanolithography as an alternative to electron-beam lithography for writing contacts to carbon nanotubes, understanding the integrity of contacts and devices patterned with this technique, and on a more fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 76 publications
3
42
1
Order By: Relevance
“…The protocol however suffers from the large number of steps necessary to realize a basic plasmonic unit and the equipment required to fabricate and characterize the circuitry. Alternatively, direct dip-pen lithography can also be utilized to realize the electrodes mitigating the need for prepatterning and the subsequent alignment steps 21 . Prealignment of the nanowires in well-defined positions would greatly reduce the fabrication time.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol however suffers from the large number of steps necessary to realize a basic plasmonic unit and the equipment required to fabricate and characterize the circuitry. Alternatively, direct dip-pen lithography can also be utilized to realize the electrodes mitigating the need for prepatterning and the subsequent alignment steps 21 . Prealignment of the nanowires in well-defined positions would greatly reduce the fabrication time.…”
Section: Discussionmentioning
confidence: 99%
“…25 These results are significantly improved over those from the best solution-processed nanotube transistors reported to date. 16,17,19,20,33 Furthermore, Figure 4d shows how L G scaling affects the low-field slope and saturation current. Note how similar the curves are for 15 and 45 nm L G devices, indicating that at low fields, scattering in the channel plays a minor role in device performance.…”
mentioning
confidence: 99%
“…Although it is well-known that Pd makes excellent contact with CVD grown large diameter CNTs, [33] however, our results need to be interpreted in the context that we are dealing with solution processed DEP assembled devices. From the study of solution processed individual CNT transistors it was found that the mobility for individual s-CNT typically varies from 10-1000 cm 2 /Vs, [32,[34][35][36] which is significantly lower than the CVD tubes where the typical mobilities are above 1000 cm 2 /Vs. [37,38] The inferior performance of the solution processed devices has been attributed to high contact resistance between the CNTs and metal contact as well as defects in the CNTs.…”
Section: Resultsmentioning
confidence: 98%